Pengaruh Kualitas Pelayanan Terhadap Kepuasan Nasabah Di Pt. Bank Central Asia (Bca) Tbk Cabang Undaan Surabaya - Yulian Belinda Rahmawati (AKRUAL: JURNAL AKUNTANSI, 2014)
AbstractThis study aims to determine the effect of Quality of Service Characteristics on Customer Satisfaction in the PT. Bank Central Asia (BCA) Branch Surabaya Undaan. The sampling in this study using stratified sampling (Stratified Random Sampling). Analysis techniques that are used are double linear regression. The calculation result shows that the quality of services simultaneous effect on customer satisfaction in PT. Bank Central Asia (BCA) Branch Surabaya Undaaan. The quality of services that include variables Responsiveness, Tangibles, Empathy, Assurance, and Reliability in a partial effect on customer satisfaction in PT. Bank Central Asia (BCA) Branch Surabaya undaaan.